A Study on Physico-Chemical Characteristics and Zooplankton Diversity (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This study was done over a year (March 2015–February 2016) and four seasons (post-monsoon,summer, pre-monsoon, and monsoon) to see if Hale Dharmapuri Lake in Dharmapuri Town is good forinland aquaculture. Quantitative identifications were made for 29 different zooplankton species,including 10 different rotifers, 8 different cladocerans, 6 different copepods, and 5 different ostracods.Rotifers had the highest average population out of all the zooplankton categories, followed byCladocerans, Copepods, and Ostracods. According to this research, zooplankton production is highestin the summer, then in the pre-monsoon, post-monsoon, and monsoon periods. Many physical andchemical factors, such as the temperature, pH, salinity, dissolved oxygen, total dissolved solids, andelectrical conductivity of lake water, were found to be linked to the number of zooplankton. All of thezooplankton species were seen in all four seasons, which suggests that the diversity index values didn'tchange much from season to season. Seasonal changes in the index value are caused by changes in thenumber of species in each group of zooplankton. There is a promise for the lake to be used for inlandaquaculture of fish and prawns since a substantial number of zooplankton species variety was observed.